2017
DOI: 10.1021/acs.iecr.7b01732
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Microwave Absorption Property of Fe Nanoparticles Encapsulated within Reduced Graphene Oxide with Different Thicknesses

Abstract: Reduced graphene oxide (RGO)/Fe nanocomposites were synthesized by a facile one-step reduction reaction, using reduced graphene oxide and FeSO 4 •7H 2 O as raw materials. These RGO/Fe nanocomposites combine Fe nanoparticles with graphene in various thicknesses. The results show that the residual defects and groups in chemically reduced graphene oxide brought about defect polarization relaxation and groups' electronic dipole relaxation, which both make the electromagnetic absorbing performance of RGO/Fe nanocom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…While, there appears a semicircle in the Cole‐Cole curve of Co 3 O 4 /Graphene as shown in Figure (b), indicating that the Debye relaxation process is reinforced enough as the graphene has been introduced. Moreover, as shown in Figure (c) and Figure (d), this polarization relaxation process can be further enhanced with the addition of MWCNTs for the specific one‐dimensional structure, it is conducive to enhance the interface polarization and dipolar polarization of ternary composite further …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While, there appears a semicircle in the Cole‐Cole curve of Co 3 O 4 /Graphene as shown in Figure (b), indicating that the Debye relaxation process is reinforced enough as the graphene has been introduced. Moreover, as shown in Figure (c) and Figure (d), this polarization relaxation process can be further enhanced with the addition of MWCNTs for the specific one‐dimensional structure, it is conducive to enhance the interface polarization and dipolar polarization of ternary composite further …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, as shown in Figure 10(c) and Figure 10(d), this polarization relaxation process can be further enhanced with the addition of MWCNTs for the specific one-dimensional structure, it is conducive to enhance the interface polarization and dipolar polarization of ternary composite further. [45] In general, the magnetic loss is mainly generated from the domain wall resonance, hysteresis loss, eddy current loss and natural resonance. The domain wall resonance usually appears at 1-100 MHz and the hysteresis loss is negligible in a weak applied field.…”
Section: Full Papermentioning
confidence: 99%
“…Moreover, because of homogenous coating of nanoparticles base on the functionalized MWCNTs through the sonochemical and solvothermal complementary methods, interfacial polarization and Maxwell-Wagner effect was reinforced that enhanced charges accumulation and microwave absorption of sample [9,13]. Magnetic loss of the spinel ferrites because of eddy current loss effect and conductive loss of the MWCNTs according to the free electron theory caused the desirable microwave absorption in this nanocomposite [9,11]. …”
Section: Microwave Absorption Propertiesmentioning
confidence: 96%
“…Modified Ba 0.2 Sr 0.2 La 0.6 MnO 3 nanoparticles have absorbed 22.36 dB at 14.78 GHz and showed that can be a promissing microwave absorber between the other magnetic nanoparticles [1]. Recently, Polyaniline, polypyrrole, graphene, and carbon nanotube as the conductive polymers were used to dielecteric loss of the microwave absorbent nanocomposite [2,3,5,[9][10][11][12]. One of the most important factors having effect on the microwave attenuation is the polimeric matrix effect of the microwave absorbent samples.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the complex permeability and permittivity are the key factors influencing the microwave attenuations given by the transmission line theory . Thus, polyaniline, SiC, polypyrrole, polythiophene, and carbon nanotube due to the dielectric properties and magnetic materials such as spinel ferrites_ENREF_16, hexagonal ferrites, Fe 0 , Co, and Ni have attracted considerable attentions. Among the dielectric materials, the 2D structures including graphene, MXenes, and graphite‐like carbon nitride play the vital role for microwave absorption and electromagnetic interference shielding.…”
Section: Introductionmentioning
confidence: 99%